Comparative analysis on the dynamic of lacrimal gland damage and regeneration after Interleukin-1α or duct ligation induced dry eye disease in mice. (July 2018) - Dietrich, Jana; Schlegel, Carlo; Roth, Mathias; Witt, Joana; Geerling, Gerd; Mertsch, Sonja; Schrader, Stefan
Abstract: The loss of functional lacrimal gland (LG) tissue causes quantitative tear deficiency and is the most common reason for the development of severe dry eye disease (DED). The induction of LG regeneration in situ would be a promising approach to curatively treat DED, but underlying mechanisms are mainly unclear. Therefore, this study aims to comparatively evaluate the dynamic of LG damage and regeneration in two mouse models in order to study mechanisms of LG regeneration. Male C57BL/6 J mice were used to induce damage to the right extraorbital LG either by a single interleukin (IL) 1α injection or a ligation of the secretory duct for 7 days. Fluorescein staining (FL) and LG wet weight were assessed. In addition, the dynamic of damage and regeneration of acini structures as well as inflammation and the appearance of progenitor cells were (immuno-) histologically evaluated on day 1, 2, 3, 5, 7 after IL-1α injection and day 3, 7, 14, 21, 28 after duct ligation (DL). While LG weight was only slightly affected after IL-1α injection, DL led to a significant decrease at day 7 followed by an increase after re-opening. Additionally, DL resulted in a more pronounced inflammatory reaction than IL-1α injection. After DL the infiltration with CD3 + T cells, CD138 + plasma cells and CD68  +  macrophages increased, while IL-1α injection only caused an infiltration with CD68  +  macrophages. Furthermore, the damage of LG structures was significantly higher after DL than after IL-1α injection. Accordingly, regeneration of LG was prolonged and only partial at day 28 after DL, whilst 5 days after IL-1α injection a complete LG completely regeneration was achieved. We also found a significantly increased number of nestin + mesenchymal stem cells in both models during injury phase. Our results showed that both models induce LG damage followed by a spontaneous regeneration of acini structures. IL-1α injection caused an immediate inflammation with a transient period of slight tissue damage. However, DL caused a more distinct tissue damage followed by a prolonged period of regeneration, which might make it appear more attractive to study regenerative therapies and their effects on LG regeneration. Highlights: Two mouse models were compared in order to study regenerative therapies. IL-1α injection caused an immediate inflammation with slight tissue damage. Duct ligation caused marked tissue damage ensued by a partial regeneration period. Duct ligation seems to be the more attractive model to study regenerative therapies. Mesenchymal stem cells appeared to be involved in LG regeneration.